Design and simulation hybrid filter for 17 level multilevel inverter - Marshal Andrea Hutabarat; Syafruddin Hasan; Ali Hanafiah Rambe; Suherman Suherman (Bulletin of Electrical Engineering and Informatics, 2020)
The increasing of renewable energy applications such as solar cells, wind power, ocean thermal and HVDC (high voltage direct current) cause increment in the use of the inverter circuit. Harmonics that are generated by the inverter have negative impacts on the electrical equipment; harmonics cause excessive heat and may shorten the life of electrical equipment. A multilevel inverter is an arranged of cascaded inverters which aims to reduce total  harmonic distortion (THD). This paper proposes the design of 17 levels of a single-phase cascaded multilevel inverter with a hybrid filter insertion. By using PSIM simulator, the hybrid filter is proven reducing THD better than single pulse width modulation (SPWM) inverter. Installation of the hybrid filter is able to fix a maximum of 0.23% THDv and a maximum of 1.05% THDi. Hybrid filter installation reduces the value of THD to comply with IEEE 519-2014 standard.